Gastroduodenal Involvement in Asymptomatic Crohn's Disease Patients in Two Areas of Emerging Disease: Asia and Eastern Europe. (9th June 2016) - Farkas, Klaudia; Chan, Heyson; Rutka, Mariann; Szepes, Zoltán; Nagy, Ferenc; Tiszlavicz, László; Nyári, Tibor; Tang, Whitney; Wong, Grace; Tang, Raymond; Lo, Angeline; Cheung, Christina; et al.
Abstract: Background: The incidence of Crohn's disease [CD] is increasing in Asia and Eastern Europe. Limited studies have reported on the frequency of upper gastrointestinal [GI] involvement in patients with CD in non-Western countries. This prospective study compared the rate of macroscopic and microscopic upper GI manifestations and Helicobacter pylori positivity in asymptomatic CD patients in Asia and Eastern Europe. Methods: Consecutive asymptomatic CD patients were prospectively recruited for upper GI endoscopy between 2013 and 2015 in Hong Kong and in Hungary. Endoscopy and biopsy findings were recorded and histology was performed to assess for H. pylori and microscopic signs characteristic for CD, using standardized diagnostic criteria. Results: One hundred and eighty CD patients [100 Hong Kong; 80 Hungary; 70.6% male; mean age, 38.5 years] and 189 controls [100 Hong Kong; 89 Hungary; 57.7% male; mean age 41 years] were included. Gastroduodenal involvement of CD was significantly higher in Hungary than in Hong Kong [16.5% vs 2.0%, p ≤ 0.001]. H. pylori positivity was significantly higher in Hungarian than Chinese CD patients [13.9% vs 4.0%, p ≤ 0.001]. Granulomas were detected in 1% in Hong Kong and 7.6% in Hungary [ p ≤ 0.001]. Chinese CD subjects had a significantly lower H. pylori positivity compared with controls [6% vs. 15%; p ≤ 0.001]. Conclusions: Upper GI CD was significantly higher in Eastern Europe than in Asia. The detection of granuloma in Hungary was similar to the literature data, whereas focal gastritis was lower than expected in both cohorts.